What is overdiagnosis and why should we take it seriously in cancer screening? - Stacy M Carter; Alexandra Barratt (Sax Institute, 2017)
Overdiagnosis occurs in a population when conditions are diagnosed correctly but the diagnosis produces an unfavourable balance between benefits and harms. In cancer screening, overdiagnosed cancers are those that did not need to be found because they would not have produced symptoms or led to premature death. These overdiagnosed cancers can be distinguished from false positives, which occur when an initial screening test suggests that a person is at high risk but follow-up testing shows them to be at normal risk. The cancers most likely to be overdiagnosed through screening are those of the prostate, thyroid, breast and lung. Overdiagnosis in cancer screening arises largely from the paradoxical problem that screening is most likely to find the slow-growing or dormant cancers that are least likely to harm us, and less likely to find the aggressive, fast-growing cancers that cause cancer mortality. This central paradox has become clearer over recent decades. The more overdiagnosis is produced by a screening program, the less likely the program is to serve its ultimate goal of reducing illness and premature death from cancer. Thus, it is vital that health professionals and researchers continue an open, scientific inquiry into the extent and consequences of overdiagnosis, and devise appropriate responses to it.